THE IMPACT OF WORKING CULTURE AND FINANCIAL COMPENSATION ON TEACHER’S JOB SATISFACTION IN JUNIOR HIGH SCHOOL PAGUYAMAN SUB-DISTRICT BOALEMO REGENCY - husainirma; Irawaty Igirisa (LP2M Universitas Bina Mandiri Gorontalo, 2021)
The impact of working culture and financial compensation on teacher’s job satisfaction in Junior High School Paguyaman sub-district Boalemo district. The study aims to know and analyze the impact of the work culture and financial compensation on teacher satisfaction at junior high school Paguyaman sub-district Boalemo district. The study employs descriptive quantitative methods. The sample in this study is a civil servant teacher at junior high school Paguyaman sub district Boalemo district. The data of analysis used multiple regressions. Research shows the work culture has positive and significant impact on teacher satisfaction. Financial compensation is significant to a teacher's job satisfaction. Work culture and financial compensation are simultaneously positive and significant to teacher satisfaction.